Stochastic Gradient-Based Extremum Seeking Control Under Multi-Input and Output System Delays - Souza Silva, Paulo Cesar; Cesar Pellanda, Paulo; Oliveira, Tiago Roux (International Conference on Control, Decision and Information Technologies (Online), 2024)
This paper presents a novel multivariable gradient-based stochastic extremum seeking control strategy capable of addressing systems with multiple inputs and time delays in both input and output channels. Key features include phase compensation of stochastic disturbance signals and a new predictor based on estimating the unknown Hessian. Rigorous analysis employing backstepping transformation and stochastic averaging techniques in infinite dimensions ensures exponential stability and convergence to a small neighborhood around the extremum point. A numerical example illustrates the effectiveness of the proposed approach for delay compensation.